Dynamic Contrast Magnetic Resonance Lymphangiography Localizes Lymphatic Leak to the Duodenum in Protein-Losing Enteropathy. Issue 1 (17th August 2021) - Brownell, Jefferson N.; Biko, David M.; Mamula, Petar; Krishnamurthy, Ganesh; Escobar, Fernando; Srinivasan, Abhay; Laje, Pablo; Piccoli, David A.; Pinto, Erin; Smith, Christopher L.; Dori, Yoav
ABSTRACT: Objectives: Protein-losing enteropathy (PLE) is a disorder of intestinal lymphatic flow resulting in leakage of protein-rich lymph into the gut lumen. Our primary aim was to report the imaging findings of dynamic contrast magnetic resonance lymphangiography (DCMRL) in patients with PLE. Our secondary objective was to use these imaging findings to characterize lymphatic phenotypes. Methods: Single-center retrospective cohort study of patients with PLE unrelated to single-ventricle circulation who underwent DCMRL. We report imaging findings of intranodal (IN), intrahepatic (IH), and intramesenteric (IM) access points for DCMRL. Results: Nineteen patients 0.3–58 years of age (median 1.2 years) underwent 29 DCMRL studies. Primary intestinal lymphangiectasia (PIL) was the most common referring diagnosis (42%). Other etiologies included constrictive pericarditis, thoracic insufficiency syndrome, and genetic disorders. IN-DCMRL demonstrated a normal central lymphatic system in all patients with an intact thoracic duct and localized duodenal leak in one patient (1/19, 5%). IH-DCMRL detected a duodenal leak in 12 of 17 (71%), and IM-DCMRL detected duodenal leak in 5 of 6 (83%). Independent of etiology, lymphatic leak was only visualized in the duodenum. Conclusions: In patients with PLE, imaging via DCMRL reveals that leak is localized to the duodenum regardless of etiology. Comprehensive imaging evaluation with three access points can provide detailed information about the site of duodenal leak.